PEDIATRICS TEACHING IN PRE-REVOLUTIONARY RUSSIA - G.L. Mikirtichan; S.L. Akimova; R.V. Suvorova ("Paediatrician" Publishers LLC, 2009)
(Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(3):148-152)